Justice With Aloha: Police Interviews of Rape Victims in Hawaii - Rich, Karen (Women & criminal justice, 2025)
Rape is widespread across the United States, yet survivors often fear making police reports. Effective police interviews can reduce the re-traumatization of survivors and result in more useful reports. However, rape survivors (most frequently women) often have difficulty accessing procedural justice. Little is known about rape processing in Hawaii, especially from the police perspective. A sample of 887 sworn police officers from the major jurisdictions in Hawaii completed a quantitative survey that measured their knowledge of interview techniques, rape myth acceptance, number of rape cases, degree of collaboration with victim advocates, and specialized training. Results indicated that low rape myth acceptance, greater amounts of specialized training, indicators of a positive agency culture, more extensive collaboration with victim advocates, higher rank, and greater experience with rape cases were positively related to interview skill. Female gender did not emerge as a significant contributor to interviewing skill. Implications of this study include the need for: training to counter specific myths, improvement of collaboration with victim advocates, careful screening of police officers assigned to conduct victim interviews, better training to respond to survivors with disabilities, and the development of a work culture supportive to citizens reporting rape.